Analysis of risk factors for capsular contracture after breast augmentation: a retrospective study - Li, Xin-Yao; Xiao, Shi-Qi (Frontiers in Surgery, 2025)
BackgroundCapsular contracture is a prevalent complication following breast augmentation that adversely affects aesthetic outcomes and often necessitates revision surgery. This study aimed to assess potential predictors of capsular contracture in patients undergoing primary breast augmentation.MethodsIn this retrospective study, 212 patients (386 implant insertions) who underwent primary breast augmentation with silicone implants at our institution between January 2019 and December 2022 were included. Patients were stratified based on the presence of capsular contracture, diagnosed and graded by board-certified plastic surgeons using the Baker classification system. Demographic, clinical, and surgical parameters—including age, body mass index (BMI), smoking history, lactation history, implant characteristics, surgical approach, and postoperative drainage volume—were recorded. Statistical analyses were performed using SPSS version 26.0 (Statistical Package for the Social Sciences). Univariate analysis was conducted with t-tests and chi-square tests, while multivariate logistic regression was applied to identify independent risk factors, with significance set at P < 0.05.ResultsUnivariate analysis demonstrated that variables such as age, BMI, and drainage volume did not significantly differ between groups. However, smoking history, oversized implants, and hematoma occurrence were significantly associated with capsular contracture. Multivariate logistic regression confirmed that a positive smoking history [odds ratio [OR] = 2.95, 95% confidence interval [CI]: 1.38–6.38], implant oversizing (OR = 6.00, 95% CI: 2.44–14.80), and hematoma formation (OR = 14.60, 95% CI: 1.78–118.90) independently increased the risk.ConclusionsThis study identifies smoking, implant oversizing, and hematoma as significant modifiable risk factors for capsular contracture following breast augmentation. These findings underscore the importance of careful preoperative planning and patient counseling to mitigate postoperative complications.